Employing "Ender's Game"Â Movie as an Aid in Character Education in EFL Classroom - Ratih Kuswidyasari (JET ADI BUANA, 2017)
21st century education appears due to the concerns related to the difficulties and challenges faced by people around the world caused by the advanced technology. Educators feel the necessity to design curriculum which prepares the students to face the rapidly changing world. One of the four dimensions in 21st century education is character education, whose purpose is similar to the purpose of education since the very beginning which is developing students to become outstanding personalities. This article focuses character education through ELT by employing a movie titled "Ender's Game"Â with the intention of attracting the students to actively participate in learning activities. The whole film approach is used to design the classroom activities relevant to the lesson objectives. The students are expected to cultivate their critical thinking, and to gain language competence focusing in speaking skill, as well as to instill character education within them. The lesson is intended for tenth grade students for the reason that the movie is appropriate for the students that age.